Collective choice and social welfare by Amartya Sen: a review essay with reference to development in Peru - Deneuin, S; Clausen, J (Oxford Poverty and Human Development Initiative, 2018)
This paper provides an overview of Sen’s revised edition of Collective Choice and Social Welfare (London: Penguin Books, 2017) and examines the relevance of its arguments in the context of Peru. It focuses on three main points: 1) a social choice approach for addressing global problems; 2) an expanded informational basis for making judgments; and 3) a public reasoning view of collective decision-making. The paper then discusses these points in relation to development policy in Peru. It critically analyses the human-social development strategy followed by the Peruvian government in recent years and, in particular, the capacity of public reasoning to reflect and sustain the priorities of the poorest and marginalized in the public policy agenda.